On the Issue of Improving Chinese EFL Learner’s Spoken Fluency - Zhao, Jun (Journal of Educational Research and Policies, 2025)
Chinese EFL learners generally underperform in speaking compared with peers from other regions, as shown by IELTS and TOEFL data. This article addresses the issue of spoken fluency – a core yet difficult aspect of oral proficiency – by exploring its cognitive and linguistic foundations and suggesting pedagogical solutions. Cognitively, fluency develops through practice that moves knowledge from declarative to automatized stages, emphasizing time pressure and continued use. Linguistically, pronunciation, lexical retrieval, syntactic structuring, and discourse management are key to fluent speech. Three pedagogical directions are proposed: (1) speed-focused approaches (e.g., 4/3/2 technique, soliloquizing) to build automaticity; (2) pattern-focused approaches (e.g., lexical and discourse-based instruction) to enhance formulaic and structural fluency; and (3) speaking-promoting approaches integrating communicative and task-based methods for meaningful interaction. The article concludes that improving spoken fluency requires more opportunities for authentic speech and balanced attention to speed, accuracy, and automaticity.